Examining the factor structure of the Rey auditory verbal learning test in individuals across the life span. Issue 4 (20th April 2020) - Weitzner, Daniel S.; Pugh, Erika A.; Calamia, Matthew; Roye, Scott
ABSTRACT: Objective : Previous studies analyzing the factor structure of the Rey Auditory Verbal Learning Test (RAVLT) have been limited in the number of scores included in the analysis. Often, they lacked inclusion of process scores that have been shown to add predictive value in identifying future cognitive decline. Therefore, the goal of the current study was to determine the factor structure of the RAVLT utilizing factor scores including serial position effects, repetitions, and intrusion errors, and to examine if the factor structure for older adults is similar to that found in the entire lifespan sample. Method : Exploratory factor analysis (EFA) was conducted on 718 participants (age 16–85 years) from the Nathan Kline Institute (NKI)-Rockland project. Confirmatory factor analyses (CFA) of a reduced model of the EFA was conducted on the entire sample and an older (ages 55–85 years; n = 265) and a younger (less than 55 years of age; n = 453) subsample. Results : EFA indicated three factors: Memory, Attention/Learning, and Inaccurate Memory (i.e., repetitions and intrusions). CFA of a reduced model indicated adequate fit in the entire sample and older subsample, and good fit in the younger subsample. Conclusion : The present study examined the factor structure of the RAVLT in a large lifespan sample utilizing a larger set of RAVLT scores than have been examined in prior studies, including total scores and process scores. The same factors were identified in the entire lifespan sample and the younger and older adult subsamples, although similar to previous studies, measures of model fit were less robust in the older adult subsample. These results provide additional support for the error scores (e.g., intrusions and repetitions) as separable from other aspects of learning and memory.